PMSM position-sensorless control method for optimizing fluctuating high-frequency signal injection - ZHANG Lei; WANG Kaifeng; LI Pengfei; XU Yanhui (Xi'an Gongcheng Daxue xuebao)
In the position sensorless control method of permanent magnet synchronous motor (PMSM) based on fluctuating high-frequency signal injection, the use of band pass filter (BPF) increases the system phase delay, resulting in poor observation performance, we proposed an optimized fluctuating high-frequency signal injection for position sensorless control method using second order-second order generalized integrator (SO-SOGI). Firstly, a method was designed to use SO-SOGI to observe PMSM rotor position and speed information. Secondly, the amplitude frequency characteristics of the SO-SOGI used at the center frequency were analyzed, and it was verified that SO-SOGI has good fundamental extraction ability and inner loop negative feedback adjustment mechanism, which can output specific frequency signals without phase delay issues. Finally, simulation verification was conducted using MATLAB/Simulink. The results show that the accuracy of rotor position estimation during static operation is improved by about 0.7rad, verifying that the method has good position estimation accuracy and improves the reliability of the system; The speed estimation error during dynamic operation is reduced by about 62.5%. The method can effectively adapt to changes at low speeds and the system's anti-interference performance is improved.